Impact of Sample Concentration on the Determination of Particle Size of Nano Polymer Particles and Nano Liposomes by Dynamic Light Scattering - Thi Hai Yen, Tran; Thi Huyen, Le; Hong Nhung, Tran; Thi Thu Trang, Le; Thi Minh Hue, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 35 No 2, 2019)
Determination of particles size is important in pharmaceutical research and manufacturing of drug delivery system in nano scale. This study was carried out to evaluate particles size of nano polymer particles, composed of Eudragit RL 100, and nano liposomes, composed of hydrogenated soy phosphatidylcholine and cholesterol. Dynamic light scaterring was used to determine nano particles size. The results showed that, dilution ratio influenced differently on the determined nanoparticles.  Liposomal suspension, which was diluted to count rate less than 170 kcps, had statistically significant larger particle than that, which had greater count rate. Polymer particles, which were diluted to count rate less than 126 had statistically significant larger particles than that, which had greater count rate. Keywords Particle size, nano polymer particle, nano liposomes, dynamic light scattering (DLS). References [1] E.H.M. Sakho, E. Allahyari, O.S. Oluwafemi, S. Thomas, and N. Kalarikkal, Dynamic Light Scattering (DLS) in: Thermal and rheological measurement techniqus for nanometerials characterization, Elsevier, Europe 2017. [2] V.X. Minh, P.T.M. Hue, Applications of nanotechnology and liposomes in Pharmaceuticals and cosmetics, Medical publishing house, Hanoi, 2013 (in Vietnamese). [3] ISO 22412:2017, Particle size analysis - Dynamic light scattering (DLS). [4] J. Panchal, J. Kotarek, E. Marszal, and E.M. Topp, Analyzing Subvisible Particles in Protein Drug Products: a Comparison of Dynamic Light Scattering (DLS) and Resonant Mass Measurement (RMM), AAPS J., 16(3) (2014) 440–451. http://doi.org/ 10.1208/s12248-014-9579-6. [5] A. Chaudhury et al, Lyophilization of cholesterol-free PEGylated liposomes and its impact on drug loading by passive equilibration, Int. J. Pharm., 430(1–2) (2012) 167–175. https://doi.org/10.1016/j.ijpharm.2012.04.036. [6] T. Ishida, H. Harashima, and H. Kiwada, Liposome clearance, Biosci. Rep., 22(2) (2002) 197–224. https://doi.org/10.1023/A:1020134521778.